Pengaruh Brand Image, Corporate Social Responsibility dan Electronic Word of Mouth (E-Wom) Terhadap Customer Loyalty Charles & Keith Mall Senayan City - Ibnu Khawari, Ridwan; Ilyas, Nofian (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This research aims to examine the effect of Brand Image, Corporate Social Responsibility and Electronic Word of Mouth (E-WOM) on the Customer Loyalty of Charles & Keith Mall Senayan City. Brand Image, Corporate Social Responsibily and Electronic Word Of Mouth (E-WOM) as exogenous variables, then Customer Loyalty as endogenous variables. This research was conducted on the customer Charles & Keith Mall Senayan City. This is the reason behind this research to meet the increasingly fierce competition and the need for better distribution methods to reduce costs and increase profits in marketing. The samples in this study were taken using the Purposive Sampling method with a sample of 146 respondents. The analysis method used is the Structural Equation Model (SEM) and uses Partial Least Square (PLS) to test the strength of direct and indirect relationships between various variables. The results of this study prove that Brand Image affects Customer Loyalty, Corporate Social Responsibilty affects Brand Image, Corporate Social Responsibility affects Electronic Word of Mouth (E-WOM) and Electronic Word of Mouth (E-WOM) affects Customer Loyalty.